THE SILENT ENEMY FROM THE FIST - VIKING DISEASE - Stoiljković, Vera (Halo 194 Scientific Journal of Emergency Medicine, 2025)
Dupuytren's contracture (DK) is a progressive idiopathic fibrosis of thesuperficial palmar fascia caused by changes in the palmar aponeurosis,resulting in flexion contracture of the fingers with inability to extend thefingers. The disease, also called Viking's disease, is present in 8% of the world's population, more commonin men, and heredity, which shows variable expression, plays an important rolein its etiology. The pathogenesis of DK is still unclear, and involves theformation of collagen nodules that progress into fibrous bands at the places ofgreatest pressure between the dermis and fascia. The diagnosis isestablished only by clinical examination, and the treatment can be conservativeand surgical. Conservative treatment is reserved for patients with mildersymptoms and no finger contracture, while surgical treatment is the goldstandard in the therapy of people in whom the resulting contracture limits thefunction of the hand and/or flexion of the proximal interphalangeal joint by≥15º and/or the metacarpophalangeal joint by ≥30º. The aim of thispaper is to present the current findings related to DK.
Keywords: Dipitren's contracture, Viking's disease, clinical picture, diagnosis, therapy